Gerenciamento de projetos com a gest??o de stakeholders: o desenvolvimento de uma associa????o de alunos e egressos em programa de p??s-gradua????o - Vieira, Alessandro de Almeida (2016)
Year after year, the kind of market where universities function has been showing an increase in competition and creating specific needs of innovation in educational management area. Researches indicate that the educational management of the universities differs from the organizational management which is conceptualized and taught to their students. The elements considered to reach this conclusion are the administrative complexity of these institutions and the diversity of actors or stakeholders in the decision-making process. Signaling from national agencies for educational control and monitoring, including the Higher Education Personnel Improvement Coordination - CAPES, responsible for evaluating Brazilian post-graduation, indicates the need for monitoring the students of these programs. This fact indicates an opportunity for innovation and differentiation in the educational market, related to administrative matters, in addition to human material capturing issues. Within this context, this study aims at answering the question ???How can project management contribute to the development of a students and graduates association, from a post-graduate studies program, based on stakeholder management????. The main objective of the study is to present a plan to develop a students and graduates association from a post-graduate studies program, based on project management and using stakeholders management. It aims at assisting in the development and growth of the association, using both the tools and concepts of project management. To answer this question and achieve the main goal, an applied research was conducted. The research was of descriptive and explanatory nature, using qualitative approach and action-research methodology. The results identified who are the stakeholders of such an association, as well as the point of view of its managers. Results also showed the contribution of a proper project management to leverage the development of the association, bringing benefits which are extensible to the higher education institution it represents.